Efektivitas Program Sistem Pelayanan Kepuasan (SIKAP) Di Kecamatan Baros Kota Sukabumi - Adiwijaya, Trisya Juliantina; Meigawati, Dine; Mulyadi, Andi (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
The aim of this research is to obtain further information about the implementation of the community service satisfaction system program in Baros District, Sukabumi City. In this research, a qualitative research methodology with a descriptive approach was used, and a purposive sampling strategy was used to identify 5 informants. For this research, researchers used interview techniques, observation methods, and documentation. Researchers also use triangulation of methods and sources to carry out the data validation process. The results of this study show that the effectiveness of the SIKAP program in Baros District, Sukabumi City, assessed from three accuracy indicators based on Duncan's theory (in Steers, 2020: 53) has not worked well, because there are still many people who do not understand how to use the application, apart from that In the implementation of socialization by internal and external parties, it has been running but is still not sustainable, which means that the public still does not understand the benefits and objectives of the Attitude program, then the facilities and infrastructure that support the implementation of this program still have many deficiencies, especially in the appearance of the Attitude program application.